Barriers to HIV testing and characteristics associated with never testing among gay and bisexual men attending sexual health clinics in Sydney. Issue 1 (27th August 2015) - Conway, Damian P; Holt, Martin; Couldwell, Deborah L; Smith, Don E; Davies, Stephen C; McNulty, Anna; Keen, Phillip; Cunningham, Philip; Guy, Rebecca; ,
Abstract : Introduction: HIV diagnoses among gay and bisexual men have increased over the past decade in Australia. HIV point‐of‐care testing (POCT) was introduced in Australia in 2011 as a strategy to increase HIV testing by making the testing process more convenient. We surveyed gay and bisexual men undergoing POCT to assess barriers to HIV testing and characteristics associated with not having previously tested for HIV (never testing). Methods: During 2011 and 2012, gay and bisexual men who were undergoing POCT at four Sydney sexual health clinics self‐completed questionnaires assessing testing history and psychological and structural barriers to HIV testing. Bivariate and multivariate logistic regression was used to assess associations between patient characteristics and never testing. Results: Of 1093 participants, 981 (89.9%) reported ever testing for HIV and 110 (10.1%) never testing. At least one barrier to testing was reported by 1046 men (95.7%), with only 47 men (4.3%) not reporting any barrier to testing. The most commonly reported barriers to testing were annoyance at having to return for results (30.2%), not having done anything risky (29.6%), stress in waiting for results (28.4%), being afraid of testing positive (27.5%) and having tested recently (23.2%). Never testing was independently associated with being non‐gay‐identified (adjusted odds ratio [AOR]: 1.9; 95% confidence interval [CI]: 1.1–3.2), being aged less than 25 years (AOR: 2.4; 95% CI: 1.6–3.8), living in a suburb with few gay couples (AOR: 1.9; 95% CI: 1.2–3.0), being afraid of testing HIV‐positive (AOR: 1.6; 95% CI: 1.0–2.4), not knowing where to test (AOR: 3.8; 95% CI: 1.3–11.2) and reporting one or no sexual partners in the last six months (AOR: 2.7; 95% CI: 1.2–6.2). Conclusions: Barriers to HIV testing were commonly reported among the clinic‐based gay and bisexual men in this study. Our findings suggest further health promotion and prevention strategies are needed to address the knowledge, attitudes and behavioural factors associated with never testing.